Challenges for gender equality: Women’s religious circles in post-revolutionary Iran - Chavoshian, Sana (My University, 2017)
The agency of women in Islamicate societies is largely anchored in ideas over pious circles and gender-specific rituals. Recent studies attest religious modes of women’s presence in the public space a high significance. Taking the case of Iran, the urging question is how and to which extent religious agency within female pious circles – which were formed before the 1978/9 Revolution and fashioned after it – has been able to attain broader civil significance beyond these circles. This study explores the inner dynamics of female pious circles among women as related to structural power relations. It spells out the process of “self-spiritualization” to characterize interactions within the circles that act as a tool for self-elevation and self-authorization and as a mode of spiritually legitimated construction of hierarchies within the circles’ spiritual empowerment. It is argued that a type of pious competition between the women unfolds leading to an affirmation of gender segregation and concomitantly, of submission to institutionalized structures of masculine hierarchy and power. Finally, it pursues the effects of unfolding “self-spiritualization” through elevation, authenticity and self-authorization that might achieve a considerable degree of self-empowerment for negotiating gender roles and political life attitudes.
Keywords: dreams; female empowerment; mothers of martyrs; Muslim’s piety; Religion; self-spiritualization; Spiritualität; women’s religious circle; ddc:303